2011
DOI: 10.4103/0971-6203.79690
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric effect of multileaf collimator leaf width in intensity-modulated radiotherapy delivery techniques for small- and large-volume targets

Abstract: The purpose of this study was to evaluate the dosimetric effect of the leaf width of a multileaf collimator (MLC) in intensity-modulated radiotherapy (IMRT) delivery techniques for small- and large-volume targets. We retrospectively selected previously treated 5 intracranial and 5 head-neck patients for this study to represent small- (range, 18.37-72.75 cc; mean, 42.99 cc) and large-volume (range, 312.31-472.84 cc; mean, 361.14 cc) targets. A 6-MV photon beam data was configured for Brianlab m3 (3 mm), Varian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
2
5
0
Order By: Relevance
“…Many previous studies have investigated the dosimetric benefits of thin-leaf MLCs in IMRT and stereotactic radiosurgery for small-volume targets. 22,38 The results of the present study are consistent with the results of these previous studies. In particular, we have confirmed that 2.5-mm MLC can provide better a CI for PTV when treating a C-shape lesion with S&S_IMRT or VMAT.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Many previous studies have investigated the dosimetric benefits of thin-leaf MLCs in IMRT and stereotactic radiosurgery for small-volume targets. 22,38 The results of the present study are consistent with the results of these previous studies. In particular, we have confirmed that 2.5-mm MLC can provide better a CI for PTV when treating a C-shape lesion with S&S_IMRT or VMAT.…”
Section: Discussionsupporting
confidence: 93%
“…25 In a study that compared 5-and 10-mm MLCs in both S&S_IMRT and sliding-window IMRT of the head and neck, the authors concluded that leaf width did not substantially affect target conformity or normal-tissue sparing. 22 In the present study, we observed similar results; dosimetric parameters did not differ significantly between 2.5-and 5-mm MLCs in either S&S_IMRT or VMAT for LH&N. Consequently, MLC leaf width could have fairly minimal effects on the dosimetric characteristics of S&S_IMRT and VMAT for LH&N, even though substantial differences were observed for C-shape targets.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…They also reported reduced dose to the spinal cord, brainstem, and parotid glands, which is consistent with our findings. Yoganathan et al, (11) however, compared the Varian 120 leaf MLC and the Varian 80 leaf MLC for five head and neck patients and reported no appreciable difference in terms of target coverage or OARs (parotids) sparing.…”
Section: Discussionmentioning
confidence: 99%
“…However, leaf interdigitation has a limitation, in that it may cause a leaf collision and increase the wear of MLCs. In fact, several researchers with different views have published regarding this topic [ 4 , 17 19 ]. However, currently, experimental investigations of the ability of MLC leaf interdigitation with inverse planning techniques for different types of tumour sites are scarce, although interdigitation is widely applied in 3D-CRT techniques.…”
Section: Introductionmentioning
confidence: 99%